TEACHING READING COMPREHENSION USING TEAM ACCELERATED INSTRUCTION (TAI) TECHNIQUE - Setiati, Euis; Satriani, Intan (ETERNAL (English, Teaching, Learning, and Research Journal), 2019)
This study aims at examining whether students’ reading comprehension can be improved by using Team Accelerated Instruction (TAI) technique. This research used pre experimental design with one group pretest and post-test. The sample of this research was 34 students of tenth grade of SMK Pasundan 1 Cimahi in academic year 2017/2018. The instrument of this research was test which consist of multiple choice question. The data of this research was collected by giving reading comprehension test to students. The collected data of this research was analyzed using SPSS program. Then, the result of data analysis showed that mean of pretest 55.59 and after the implementation of Team Accelerated Instruction (TAI) technique the mean of posttest became 67.79. It shows that there are significant differences between pretest and posttest. Based on the data analysis, the null hypothesis was rejected. In other words, teaching reading comprehension using Team Accelerated Instruction (TAI) technique had significance improvement on students’ reading comprehension. The implementation of Team Accelerated Instruction (TAI) technique in teaching reading comprehension was able to resolve those difficulties since it required the students to share, discuss, and unite their thought or problem on comprehending the content of the text with other members of their group.